2010
DOI: 10.3390/sym2021099
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Asymmetry in Flies, What Does It Mean?

Abstract: Abstract:The degree of departure from perfect symmetry in organisms, fluctuating asymmetry (FA), is seen in most populations of animals. It has particular impact on choice of mate which lies within the world of sexual selection. Here I consider a relatively little studied aspect of sexual selection, i.e. the effect of FA on contests between males for mates, based not on display ornament but rather on agility seen in the mating systems of many insects. The model organism considered is the ubiquitous chironomid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Importantly, although the RDA suggested that the effect of wing (left or right) was not significant when considered with species, sex or species × sex (Table S1) inspection of mean PCA values (Figures S1 & S2) suggests that there may be intra‐sexual differences in mean WIP colour and WIP colour contrast between left and right wings. Asymmetries in wing morphology have been widely reported in flying insects (Koshio et al., 2007; McLachlan, 2010; Windig & Nylin, 1999), and it is therefore likely that asymmetries in WIPs are also widespread. It is important that future studies consider asymmetries between left and right wings when assessing WIP variation—particularly considering that the symmetry of left and right WIPs may signal individual quality (Møller & Pomiankowski, 1993; Uetz & Smith, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, although the RDA suggested that the effect of wing (left or right) was not significant when considered with species, sex or species × sex (Table S1) inspection of mean PCA values (Figures S1 & S2) suggests that there may be intra‐sexual differences in mean WIP colour and WIP colour contrast between left and right wings. Asymmetries in wing morphology have been widely reported in flying insects (Koshio et al., 2007; McLachlan, 2010; Windig & Nylin, 1999), and it is therefore likely that asymmetries in WIPs are also widespread. It is important that future studies consider asymmetries between left and right wings when assessing WIP variation—particularly considering that the symmetry of left and right WIPs may signal individual quality (Møller & Pomiankowski, 1993; Uetz & Smith, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…thermal regulation), the effect of energetic costs on fitness-related traits such as fecundity depends on how such costs interact with these traits. Moreover, dispersive capacity of melanic individuals may be mechanically compromised due to their less symmetrical wings, considering flight performance and wing function [87].…”
Section: Discussionmentioning
confidence: 99%
“…Symmetry is important for the movement of an animal, reveals its physiological state, and it also plays an important role in reproduction, courtship, and reproductive behavior [ 63 , 64 , 65 ]. The results of our research indicated that neomycin causes significant stress for larvae and imagoes of D. melanogaster .…”
Section: Discussionmentioning
confidence: 99%